Efforts to Improve Understanding of Asmaul Husna by Using the Numbered Head Together Learning Model in Madrasah Ibtidaiyah - Ali Arwani, Ahmad (FITK UIN Walisongo Semarang, 2024)
This research aims to improve the understanding of Asmaul Husna in Madrasah Ibtidaiyah through the application of the Numbered Head Together (NHT) learning model, a cooperative method that emphasizes the active participation of all students in the learning process. Education, in this context, is seen as a conscious and planned effort that aims to shape the character and behavior of students to be in accordance with Islamic values. The process of developing students' intellectual potential needs to be accompanied by the cultivation of moral values and manners, such as manners, which are an inseparable part of a Muslim's personality. The NHT model was applied because it was found that the students at Madrasah Ibtidaiyah were still not optimal in creative thinking, and were not fully aware of the importance of manners in daily life. The research method used is Classroom Action Research (PTK) with a cycle design consisting of three main stages: planning, implementation, and reflection. At the planning stage, the researcher developed a Learning Implementation Plan (RPP) which includes learning activities using the NHT model and evaluation instruments. During the implementation, students are divided into small groups and actively participate in group discussions and presentations of the results of the discussion. Observations were made to evaluate students' activeness and understanding of Asmaul Husna's material. The data collected from observations and comprehension tests were then analyzed to determine the effectiveness of the NHT model. The results of the study showed a significant increase in the understanding of Asmaul Husna, accompanied by an increase in the activeness and polite behavior of students. This method has proven to be effective in achieving the learning goals that have been set, which is not only improving students' cognition, but also their affective aspects.